Integrative taxonomy of the Italian pine voles, Microtus savii group (Cricetidae, Arvicolinae). (28th November 2015) - Bezerra, Alexandra M. R.; Annesi, Flavia; Aloise, Gaetano; Amori, Giovanni; Giustini, Leonardo; Castiglia, Riccardo
Abstract : The Italian endemic voles belonging to the Microtus savii group (de Sélys‐Longchamps, 1838) include five controversial taxa, namely M. savii savii, M. s. niethammericus Contoli2003 ; M. s. tolfetanus Contoli2003, M. s. nebrodensis ( Minà‐Palumbo, 1868) and M. brachycercus (Lehamann, 1961). A previous mtDNA phylogenetic analysis revealed three main mtDNA lineages that do not correspond to the recognized taxa. Here, we perform a comprehensive univariate and multivariate analysis of craniodental measurements in 151 specimens from 54 geographic samples belonging to the three main phylogroups. Qualitative data on the skull of 126 specimens were also obtained from 54 localities. Moreover, we sequenced the nuclear DNA β ‐fibrinogen intron 7 ( β‐fibint7 ) of 23 specimens from 12 localities and Cyt b sequences of 11 new specimens from seven localities. The pattern of morphological and cytogenomic divergence does not corroborate the current taxonomic framework and indicates that M. nebrodensis is a Sicilian endemic species.